Effectiveness of Thicker Hamstring or Patella Tendon Grafts to Reduce Graft Failure Rate in Anterior Cruciate Ligament Reconstruction: A Systematic Review - Alsalmi, Ahmed Atiah; Almalki, Meshari Musaad; Alsufyani, Emad Ruddah; Ahmad, Tayyab (International Journal of Innovative Research in Medical Science, 2022)
Introduction: In this systematic review, graft failure of two types of grafts (hamstring or patella tendon grafts) that are used for surgical reconstruction of the anterior cruciate ligament are reported and compared. Methods: This is a systematic review which is conducted in PubMed depending on preferred reporting item for systematic reviews and meta-analysis (PRISMA) criteria. We included a total of 19 studies which reported graft failure rates of at least one of the anterior cruciate ligament reconstruction methods mentioned above. To be able to compare studies with different follow-up periods, a yearly graft failure rate for each reconstruction group was calculated and then investigated for significant differences by using the Kruskal–Wallis test. Results: Overall, a total of 1366 patients treated with an anterior cruciate ligament reconstruction were included in the calculations. Comparison of graft types showed that hamstring tendon autografts had a yearly graft failure rate of 1.7 % in patients treated with Double-bundle hamstring autograft, 1.68 % among patients treated with single-bundle hamstring autograft and 1.6 % in patients with patellar tendon autograft. Conclusion: The results of this systematic revie showed that there is no significant difference in the graft failure rates per year among hamstring tendon autograft and bone–patellar tendon–bone autograft. Based on the results of this review, all graft options found to deliver comparable results in terms of graft failure rates and thus all graft type could be considered as reliable option for ACLR with superiority to hamstring tendon autograft.